THE 5F STEPs SUPERVISORY MODEL THAT IMPACTS STUDENTS’ THAI LANGUAGE LERNING ACHIEVEMENT - Wongsa, Phitsamai (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) study the problems, causes, and solutions concerning the learning achievement of students in the Thai language subject; 2) develop and validate a 5F Steps Supervision Model that enhances students’ learning achievement in the Thai language subject; and 3) study the effects of implementing the 5F Steps Supervision Model on students’ learning achievement in the Thai language subject. The methodology employed was action research, conducted in three phases. Phase 1 involved investigating the existing problems, their causes, and potential solutions through documentary analysis, along with brainstorming sessions with 7 teachers and 5 experts. The research instruments were meeting records and data logs, with data analyzed using percentages and content analysis. Phase 2 focused on the development and validation of the model. This involved a review of relevant literature, multiple case studies of three model schools, an academic seminar with 6 experts, and a quality assessment of the draft model. The model was validated for its accuracy by 5 specialists, and for its appropriateness, feasibility, and utility by 60 practitioners. Further refinement was conducted through a focus group discussion with 9 experts and a pilot study in a non-target school. The research instruments included field study forms, the draft model and its accompanying documents, seminar records, model validation forms, and focus group discussion records. Data were analyzed using mean scores and content analysis. Phase 3 involved studying the effects of the model’s implementation. This phase assessed the supervision process, the quality of the outputs (product), and teacher satisfaction among 6 Thai language teachers at Watbansa School during the 2023 academic year. The quality of the outcomes was evaluated based on the learning achievement of 105 students from grades 1-6 at the same school. The research findings were as follows: 1) students’ learning achievement in the Thai language subject was at a good level (Grade 3) but did not meet the school’s target. The primary causes were identified as teachers’ lack of knowledge in active learning strategies and a lack of continuous instructional supervision. The proposed solutions were to promote professional development for teachers on active learning and for school administrators to implement consistent supervision. 2) The developed model consists of four main components: Principles, Objectives, Process, and Measurement & Evaluation. The core process comprises five steps (5F): Focus on Awareness, Form Plan, Foster to Practice, Follow Up and Evaluate, and Feedback and Admire. The quality assessment of the draft model was rated at the highest level for accuracy, appropriateness, feasibility, and utility. 3) The implementation results revealed that the quality of the supervision process was at an excellent level; the quality of the output was rated as passing the criteria; students’ learning achievement (the outcome) reached a good level (Grade 3), meeting the school’s target; and the teachers satisfaction with the model was at the highest level.